Representation of mental illness in video games beyond stigmatization - Kasdorf, Ruth (Frontiers in Human Dynamics, 2023)
The representation of mental illness is part of many video games; however, it is often accompanied by stigmatization and discrimination of those affected. Recently a more positive approach can be found, including a dimensional representation of mental disorders such as depression or anxiety, especially in games by independent developers. The study examined the most popular video games of 2018 and 2019 based on their representation of mental illness in a mixed-method approach. A quantitative coding process examining general aspects of the games, the characters affected, and the illness representation, is followed by a qualitative video game analysis of games in the sample with a dimensional representation of mental illness. 16 of the 74 games examined included characters affected. For the most part, mental illness is an essential aspect of the games analyzed in the sample represented by the main characters. However, the depiction of mental illness often lacks depth and dimensionality. Two examples in the study offer a dimensional representation that includes mental illness as characters, as part of the environment and atmosphere, and provide illness-related advice as part of the gameplay. These findings contribute to a more dimensional and empathetic portrayal of mental illness and reduce discrimination and stigmatization of those affected. Additionally, the category system used in this study is adaptable to future qualitative research on the MI representation of video games.